100% human milk diet: an integral part of nutrition management in NICU: PAN India neonatologist’s survey - Wazir, Sanjay; Ershad Mustafa, Syed; Reddy, Vikram K. (International Journal of Contemporary Pediatrics, 2021)
Background: Exclusive human milk diet (EHMD) benefits preterm infants the most, particularly in neonatal intensive care unit. EHMD is dependent on multiple factors consisting of breastfeeding awareness, availability of pasteurized donor human milk, functioning human milk banks and infrastructure. Neonatal nutritional practice varies considerably in India. The aim of this survey was to understand the implementation and benefits of 100% human milk diet through human milk derived nutritional products in preterm infants from NICU experts’ perspective. Methods: The online survey questionnaire formulated and reviewed by the expert neonatologists was shared with the NICU experts pan India through multiple communication channels and referrals. The survey was constructed on the Google Forms platform, the responses was collected between May 2020 to July 2020. Results: A total of 100 neonatologists responded to the survey from 79 hospitals and 31 cities across India. All the respondents (100%) opined that EHMD is important for preterm infants, 15% opined that EHMD was ensured to all preterm infants, 80% opined that human milk-based fortifier (HMBF) was safe and well tolerated by premature infants, 17% reported that 51-80% of preterm infants experience feed intolerance issues with bovine milk based fortifiers (BMBF), blood urea nitrogen (49%) was chosen as an optimal biochemical parameter for assessing protein utilization in NICU, 93% opined that post discharge nutritional supplementation is required for preterm infants among which 49% respondents opined that HMBF and human milk 70 calorie sachet would be preferable as post discharge nutritional supplementation. Conclusions: EHMD unequivocally offers multiple benefits to preterm infants and hence needs to be included in the NICU protocol, availability of human milk derived nutritional products such as HMBF are termed safe and well tolerated and would aid in implementing EHMD in NICUs. Pasteurized donor human milk is vital for ensuring EHMD, thus access to the same needs to be empowered by strengthening the human milk donation and awareness measures.